Evaluation of a Red Grape Marc Extract as a Natural Nitrification Inhibitor and Its Effect on Soil Bacterial Community - Maldonado-Soto, J (Springer Science and Business Media Deutschland GmbH, 2023)
In intensive agriculture, nitrogen fertilization efficiency is usually low. One of the main causes of this is the leaching of nitrates, since nitrate has a weak affinity with the mineral complexes present in the soil. One alternative to reduce nitrogen leaching is to fertilize with ammonium with nitrification inhibitors because it provides more stability of N in soils. The aim of this investigation was to assess the effectiveness of a grape marc extract as a natural nitrification inhibitor and to determine its effect on the soil bacterial population. A pot experiment was established to evaluate the ammonium and nitrate concentrations in the soil after applying the treatments: (1) soil without nitrogen application; (2) soil treated with ammonium sulfate (AS); (3) soil treated with AS + dimethylpyrazole phosphate; (4) soil treated with AS + natural nitrification inhibitor (NNI) at 1.25%; 5) soil treated with AS + NNI at 2.5%. Bacterial diversity was studied using 16S rRNA sequencing on the Illumina MiSeq platform. AS+NNI-1 was able to reduce the ammonium loss rate in soil on day 31 and reduce the OTUs number of Nitrosospira and Nitrospira bacteria until days 10 and 4, respectively. Similarly, the application of DMPP maintained the highest ammonium concentration during the experiment, reducing the OTUs number of Nitrosospira and Nitrobacter. Meanwhile, AS+NNI-2 did not modify the soil ammonium concentration; however, it was able to reduce the OTUs number of Nitrospira until day 10. The use of grape marc extract showed a slight effect in reducing the ammonium loss rate in the soil, reducing the OTUs number of some nitrifying bacteria genera. © 2023, The Author(s) under exclusive licence to Sociedad Chilena de la Ciencia del Suelo.